Optimal cluster head deployment in heterogeneous wireless sensor networks - LIU Lin1; YU Hai-bin2 (Tongxin xuebao)
Cluster-based method has better adaptability and energy-efficiency to wireless sensor networks（WSN） used for environmental monitoring.If the cluster head is served by more powerful node,the performance of WSN will be improved greatly.In large scale WSN,high-power cluster head deployment is a kind of NP-hard problem.The optimal problem of cluster head deployment was formulated as an integer programming with the condition of restrictions of cluster head capacity and the maximal cluster radius.To satisfy the time effectiveness,a heuristic algorithm called KMSA was proposed which was a hybrid algorithm of K-mean and simulated annealing.The simulation results show that the KMSA can improve the performance of WSN on varieties of network size and cluster number.